The Relationship between Body Mass Index and Hemoglobin Levels in Young Girls at SMA Muhammadiyah 7 Yogyakarta - Amalia Nafisa nafisa; Budi Rahayu (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Background: Anemia is a health problem in Indonesia. Based on the 2018 Riskesdas data, the prevalence of anemia in adolescents is 32%, with mostly young women experiencing it. Anemia is often associated with nutritional problems, namely a lack of nutrients, especially iron, which can cause anemia. Adolescents need nutrition to assist in growth and development. To monitor a person's nutritional status can be done using the body mass index (BMI). Purpose: To determine the relationship between body mass index (BMI) and hemoglobin levels in class XI SMA Muhammadiyah 7 Yogyakarta. Methods: This study used an analytic observational research method with a cross-sectional design. Samples were taken using the total sampling technique, namely 28 female students. Data collection was carried out by measuring body mass index and examining hemoglobin levels, as well as data analysis using bivariate analysis of the Spearman-Rho correlation test. Results: The results showed that 2 people (7.1%) with a very low BMI had mild anemia, 1 person (3.6%) with a very thin BMI had moderate anemia, 2 people (7.1%) with a low BMI had moderate anemia, and 5 people (17.9%) with a normal BMI had mild anemia. The results of the Spearman Rho test data analysis showed that there was a relationship between body mass index and hemoglobin levels, with a significance value of p = 0.002 (p <0.05). Conclusion: There is a relationship between body mass index and hemoglobin levels in young women in the SMA Muhammadiyah 7 Yogyakarta.